PELATIHAN MANAJEMEN KEUANGAN SEDERHANA UNTUK USAHA KECIL DAN MENENGAH DI KAWASAN WISATA PANTAI BIRU MAKASSAR - Andriani Yasin, Nurfatwa; Afriyani, Afriyani; Muliati, Muliati; Jumria, Jumria (Unit Publikasi dan Jurnal Sekolah Tinggi Ilmu Ekonomi Tri Dharma Nusantara Makassar, 2025)
Small and Medium Enterprises (SMEs) are an important sector in the local economy, especially in the Pantai Biru Makassar tourist area. However, most SMEs in this area still face obstacles in managing business finances, such as no cash flow recording, mixing personal and business finances, and low understanding of basic financial management. This community service activity aims to improve literacy and skills of SMEs in managing finances through simple financial management training. The methods used include initial observation, module preparation, face-to-face training, direct practice, evaluation, and mentoring. The activity was carried out for two days in the Bira Village Hall, Makassar, involving 25 SMEs as participants. The evaluation results showed a significant increase in participants' understanding of financial recording and business financial planning. The majority of participants also started implementing routine cash flow recording after the training. This activity proves that simple financial management training can be a strategic step to encourage the sustainability and professionalism of SMEs in tourist areas. Further training and ongoing mentoring are needed so that the benefits of the training can be felt in the long term.